Consumer behavior towards online shopping in Malaysia / Ahmad Zulkarnain Abdul Aziz and Mohamad Safwan Mohamad Asraff - Abdul Aziz, Ahmad Zulkarnain; Mohamad Asraff, Mohamad Safwan (2013)
This research conducted focusing on “Consumer Behavior towards Online Shopping in Malaysia”. Since the internet is one of the ways in business activity and transaction, it is important to know about the consumer behavior in online shopping. The objective of this study (1) To identify the factors that influence consumer behavior towards online shopping in Malaysia. (2) To identify the level of consumer behavior in online shopping. (3) To examine the relationship between the factors and consumer behavior in online shopping in Malaysia. The respondents of this study were those that age 18 to 25. 100 questionnaires had been distributed among them. The researcher had used convenience sampling as the sampling technique. The process of analyzing and interpreting data has been presented by tables and figures using method of analysis such as reliability analysis, frequency analysis, descriptive analysis, and correlation analysis. The recommendations are for the company that provide online business, the consumers that are using online shopping and for the researcher to gain more information about this field of study. Researcher achieves all objective which for the first objective, is to identify the factor that influences consumer behavior towards online shopping in Malaysia. The second objective was to identify the level of consumer behavior towards online shopping in Malaysia. The third and last objective was to examine the relationship between dependent variables (consumer behavior) and independent variables (attitude towards online shopping, online shopping motivation and online information search).